STUDY ON THE UTILIZATION OF BLACK SOLDIER FLY (HERMETIA ILLUCENS) LARVAE AS BIOCONVERSION AGENT FOR ORGANIC WASTE - Joy Nardpaska Purba, Uios
Organic waste bioconversion using Black Soldier Fly (BSF) larvae is a waste processing technology that has high economic value, and can be industrialized. BSF larvae industry is a developing industry and requires optimization to be effective in processing organic waste while being economically viable. This study aims to determine the effect of waste type and number of BSF larvae on waste reduction, BSF larvae length and BSF larvae total weight. This research was conducted at TPST 3R Mutiara Bogor Raya (MBR), Bogor City. Waste samples and BSF larvae were obtained from waste sorting unit and BSF breeding unit in TPST 3R MBR. This study used experimental method with a factorial Completely Randomized Design with two factors, namely waste type, consisting of food waste, fruit peels and vegetable pieces, and number of BSF larvae, consisting of 500, 1000, and 1500 BSF larvae. Data were analyzed using ART ANOVA and Two-way ANOVA, followed by Tukey's HSD test. In this study, waste type affects waste reduction (p = 0.002), BSF larvae length (p < 0.001), and BSF larvae total weight (p = 0.003), while number of BSF larvae affects waste reduction (p < 0.001), BSF larvae length (p < 0.001), and BSF larvae total weight (p < 0.001).